THE PATTERN OF RELIGIOUS MODERATION AMONG DAYAK MERATUS CONVERT FAMILY IN PARAMASAN DISTRICT, BANJAR REGENCY - Mahmudah; Tamjidnor (RADJA PUBLIKA, 2026)
This study examines the pattern of religious moderation (Wasatiyyah and Tawazun) among the Dayak Meratus Muslim convert (mualaf) family in Paramasan District , a multi-religious area. Converts maintain strong kinship ties and live harmoniously with non-Muslim family members, practicing high tolerance and social values. They actively assist in community preparations and customary ceremonies of other religions through collective work (gotong royong) and providing aid, while maintaining religious boundaries by avoiding sacred rituals. Supporting factors for this moderation include the shared Dayak tribe and open-mindedness. Inhibiting factors are the economic, educational, and accessibility issues for routine religious guidance.